FACTORS INFLUENCING ONLINE FOOD DELIVERY ADOPTION AMONG UNDERGRADUATE STUDENTS IN KUALA LUMPUR CAPITAL, MALAYSIA - Ayedh , Shada Ali Abdo Melhi (Electronic Journal of Business and Management, 2022)
The purpose of this study is to examine the influence of customer preference, attitudes, and interpersonal influence on online food delivery adoption. The Technology Acceptance Model (TAM) was applied to explain the attitudes of undergraduate students. Using a convenience sampling method, primary data was collected from 231 undergraduate students via an online survey. The data was analyzed using descriptive statistics in SPSS software. The findings revealed that while all independent variables (customer preference, attitudes, and interpersonal influence) were significant predictors, attitudes had the most significant influence, followed by customer preference. The results provide strategic insights for E-businesses to improve adoption rates among the student demographic.